2022
DOI: 10.1038/s41419-022-05245-2
|View full text |Cite|
|
Sign up to set email alerts
|

N6-methyladenosine modification of circ_0003215 suppresses the pentose phosphate pathway and malignancy of colorectal cancer through the miR-663b/DLG4/G6PD axis

Abstract: Circular RNAs (circRNAs) are a recently discovered kind of regulatory RNAs that have emerged as critical biomarkers of various types of cancers. Metabolic reprogramming has gradually been identified as a distinct hallmark of cancer cells. The pentose phosphate pathway (PPP) plays an indispensable role in satisfying the bioenergetic and biosynthetic demands of cancer cells. However, little is known about the role of circRNAs and PPP in colorectal cancer (CRC). The novel circ_0003215 was identified at low levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Recently, the tumor-suppressing function of circ0003215 in CRC proliferation, invasion, and migration has been demonstrated. Importantly, YTHDF2 promotes the RNA degradation of circ0003215 (78). The above studies highlight the important roles of YTHDF2 in promoting CRC proliferation and tumorigenesis.…”
Section: Effects Of Ythdfs On Crcmentioning
confidence: 68%
“…Recently, the tumor-suppressing function of circ0003215 in CRC proliferation, invasion, and migration has been demonstrated. Importantly, YTHDF2 promotes the RNA degradation of circ0003215 (78). The above studies highlight the important roles of YTHDF2 in promoting CRC proliferation and tumorigenesis.…”
Section: Effects Of Ythdfs On Crcmentioning
confidence: 68%
“…Meanwhile, inhibition of G6PD can lead to accumulation of reactive oxygen species, induce endoplasmic reticulum stress, and slow the growth and migration of cancer cells [ 9 , 37 ]. G6PD ubiquitination inhibits the PPP pathway and the malignant phenotype of tumors [ 38 ], reflecting its importance in PPP regulation and subsequent tumorigenesis. Interestingly, we show here that the p52-ZER6-mediated regulation of G6PD, and subsequently the PPP, is independent of p53.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification data are expressed as mean ± SD (n = 3, unless otherwise indicated). shp52: shRNA expression vector targeting p52-ZER6; pcCon: pcEF9-Puro; pcp52: p52-ZER6 overexpression vector; **P < 0.01; ***P < 0.001. phenotype of tumors [38], reflecting its importance in PPP regulation and subsequent tumorigenesis. Interestingly, we show here that the p52-ZER6-mediated regulation of G6PD, and subsequently the PPP, is independent of p53.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Chen B et al. ( 121 ) reported the down-regulation of circ_0003215 in CRC, which was negatively correlated with tumor size, TNM stage, and lymph node metastasis. The authors found that the decrease in circ_0003215 level was due to the RNA degradation by m6A read-write protein YTHDF2.…”
Section: The Expression Of Circrna In Crcmentioning
confidence: 98%